Mapping of biguanide transporters in human fat cells and their impact on lipolysis. Issue 10 (5th July 2018) - Arner, Peter; Kulyté, Agné; Batchelor, Kenneth; Laurencikiene, Jurga; Livingston, James; Rydén, Mikael
Abstract : Aim: To examine the cell membrane transporters involved in mediating the antilipolytic effect of biguanides in human fat cells. Materials and methods: Gene expression of biguanide transporters was mapped in human subcutaneous adipose tissue and in adipocytes before and after differentiation. Those expressed in mature fat cells were knocked down by RNA interference (RNAi) and the antilipolytic effects of metformin and two novel, highly potent biguanides, NT1014 and NT1044, were examined. Results: Analysis of the transporter affinity of biguanides in HEK293 cells overexpressing individual transporters showed that NT1014 and NT1044 had >10 times higher affinity than metformin. Animal studies showed that NT1014 was >5 times more potent than metformin in lowering plasma glucose in mice. In human fat cells, the novel biguanides displayed higher AMP‐activated protein kinase activation and antilipolytic efficacy than metformin. Five transporters, organic cation transporter (OCT)1 ( SLC22A1 ), organic cation transporter novel type 1 (OCTN1; SLC22A4 ), OCT3 ( SLC22A3 ), plasma membrane monoamine transporter (PMAT; SLC29A4 ) and multidrug and toxin extrusion transporter (MATE1; SLC47A1 ), were detectable in fat cells but only OCT3, PMAT and MATE1 increased during adipogenesis in vitro and were enriched in fat cells compared with other adipose cell types. Gene knockdown by RNAi showed that MATE1 and PMAT reduction attenuated the antilipolytic effect of metformin but only PMAT knockdown decreased the effect of all three biguanides. Conclusions: While human fat cells primarily express three biguanide transporters, our data suggest that PMAT is the primary target for development of fat cell‐specific antilipolytic biguanides with high sensitivity and potency.